The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1002/glia.20256
|View full text |Cite
|
Sign up to set email alerts
|

Unique expression and localization of aquaporin‐ 4 and aquaporin‐9 in murine and human neural stem cells and in their glial progeny

Abstract: Aquaporins (AQP) are water channel proteins that play important roles in the regulation of water homeostasis in physiological and pathological conditions. AQP4 and AQP9, the main aquaporin subtypes in the brain, are expressed in the adult forebrain subventricular zone (SVZ), where neural stem cells (NSCs) reside, but little is known about their expression and role in the NSC population, either in vivo or in vitro. Also, no reports are available on the presence of these proteins in human NSCs. We performed a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
54
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 51 publications
5
54
0
Order By: Relevance
“…AQP4 is one of the predominant aquaporins in ANSCs as well as in astrocytes in the brain (Cavazzin et al, 2006). In the present study, we showed that AQP4 knockout inhibited proliferation, migration and neuronal differentiation of ANSCs in vitro.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…AQP4 is one of the predominant aquaporins in ANSCs as well as in astrocytes in the brain (Cavazzin et al, 2006). In the present study, we showed that AQP4 knockout inhibited proliferation, migration and neuronal differentiation of ANSCs in vitro.…”
Section: Discussionsupporting
confidence: 63%
“…In the damaged brain, adult neurogenesis is also found in the neocortex, striatum, amygdala and substantia nigra (Gould, 2007) where AQP4 has a high level of expression. Finally, it is reported that AQP4 is the main subtype of aquaporin in adult neural stem cells (ANSCs) (Cavazzin et al, 2006;La Porta et al, 2006;Schwartz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, AQP4 may participate in adult neurogenesis by regulating astrocytic function. More importantly, AQP4 is the main subtype of AQP in ANSCs (Cavazzin et al, 2006). However, it is unclear whether AQP4 involves adult hippocampal neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In cells expressing these channels, the direction of the water flux is determined only by the osmotic gradient. Underscoring the importance of the process of water exchange in these populations, it was found that a lack of aquaporin 4, expressed in ependymal cells and in neurosphere precursors derived from adult stem cells, leads to a functional and structural breakdown of the ependyma and to an impairment of multiple aspects of neural precursor growth in vitro [40]. Therefore, our observations that GABA A R activation promotes osmotic swelling in prominin þ precursors suggest the possibility that GABA participates in the regulation of osmotic tension in this specialized subset of precursors.…”
Section: Discussionmentioning
confidence: 99%